United Kingdom : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES The economy has rebounded strongly and prospects are promising. Headwinds that previously held back the economy-relating notably to credit conditions and confidence-have eased. Nonetheless, sustaining strong growth will depend on a recovery in productivity growth and further demand rebalancing. The housing market brings risks of financial vulnerabilities. Sterling is moderately overvalued. The overall policy mix is appropriate, but policy settings might need to be adjusted quickly. Effective monetary conditions are very supportive, compensating for ongoing fiscal consolidation: ? Accommodative monetary policy is appropriate for now, given weak inflation pressures, but policy might need to be adjusted quickly if inflation takes off. Interest rate increases may also need to be considered if macroprudential tools are insufficient to deal with financial stability risks from the housing market. ? The authorities have recently implemented macroprudential measures, including limiting the share of high loan-to-income mortgages lenders can issue, establishing them as the primary defense against housing-related risks. They should stand ready to tighten these limits should current settings prove ineffective in reining in those risks. ? A lasting solution to house price pressures requires measures to address insufficient supply. Significant planning reforms have been undertaken, but political consensus is needed to make further progress in this area. ? High deficits and rising debt mean that fiscal consolidation needs to continue. The pace and composition of deficit reduction over the near term is appropriate. Further reducing the deficit over the medium term will be challenging; both revenue and expenditure measures should be considered, keeping in mind both equity and efficiency. ? The financial sector is more robust, the new financial architecture is settling in, and significant changes have been made to banks' liquidity backstops to adapt to changing needs. Implementing macroprudential policy will be a test of the new architecture. Some problems-such as Too Important To Fail and bank misconduct- persist, and new challenges, such as from shadow banking, are emerging.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet